Simultaneous Spectrophotometric Determination of Ofloxacin and Tinidazole from Combined Dosage Forms from Pharmaceutical Formulations - Bhanu Prasad, A.; Rami Reddy, N.; Vijaya Bhaskar Reddy, Y.; Chakravarthy, I.E. (Asian Journal of Chemistry, 2016)
A new spectrophotometric method for the simultaneous and separate estimation of ofloxacin and tinidazole in binary tablet formulations has been described. The method is based on the estimation of one drug in presence of another drug by absorbance difference method. The ofloxacin solution was scanned over the range 23–390 nm and tinidazole solution was scanned over the range 220–395 nm. In this method, two wavelengths 270 and 300 nm were selected for ofloxacin. At these wavelengths the absorbance was almost zero and in case of tinidazole there should be a considerable absorbance difference. Similarly, the two wavelengths 280 and 335 nm were selected for tinidazole; at these two wavelengths the absorbance difference was almost zero and there should be considerable absorbance difference in case of ofloxacin. In the mixture of ofloxacin and tinidazole solution the absorbance values of four wavelengths 270, 300, 280 and 335 nm were measured. The amount of tinidazole is directly proportional to the absorbance difference between 270 and 300 nm. Similarly the amount of ofloxacin is directly proportional to the absorbance difference between 280 and 335 nm.